(untitled) (Journal of history, 2021)
Anthropological “other” perspective is an objective bystander perspective, which is different from the “self-beautification” of the “first person” perspective and the “opposition” and “negation” of the “second person” perspective. It is the neutral position of participatory investigation in anthropology. This paper is based on the anthropological field work in Kazakhstan from October 2019 to August 2020 by author, and mainly research on the ethnography of the museums in Almaty. Specifically, this article focuses on the ethnographic narrative of Kazakhs and traditional Kazakh culture in the Museum of Kazakhstan, the artistic narrative method that complements the narrative text of the museum, and the museumization process of Kazakhstan’s rich natural heritage to present Kazakhstan. Through the above content, to show how the Kazakhstan Museum to show how the Kazakhstan Museum “pre- serves and inherits” the material culture of the ancestors, and how to show us its spiritual culture through “exhibition”. In Kazakhstan, for many centuries, he determined the main components of the life-supporting system – housing, utensils, food, clothing, as well as the structure and functions of peculiar trades and crafts, tools, architecture and applied arts. Therefore, this paper itself is also an ethnography of Kazakhstan museums. Key words: Anthropology, “The Other”, Kazakhstan, Ethnography of Museum.